Concurrent Infection of Anaplasmosis and Babesiosis in a Cow - A Case Report - Indu Yadav; M. K. Vijayasarathi; S.Anandu (The Indian Veterinary Journal, 2024)
A two calved cross-bred Jersey cow (5 years) was presented at Referral Veterinary Clinical Complex, Indian Veterinary Research Institute, Izzatnagar during the month of August 2023 with history of high fever, coffee coloured urination, anorexia, and low milk yield. Clinical examination revealed pyrexia (105.8), haemoglobinuria, enlarged prescapular lymph node, pale vaginal and conjunctival mucous membranes, and presence of ticks over the body. Blood smear was screened for parasitological examination using Giemsa’s stain which showed positive for Babesia bigemina and Anaplasma marginale mixed haemoprotozoan infection. The cow was treated with diminazine aceturate @ 3.5 mg/kg I/M and oxytetracycline @ 20mg/kg body weight, along with supportive therapy against babesiosis and anaplasmosis respectively showed progressive recovery after 5 days of treatment. Incidence of concurrent infection of Babesiosis and Anaplasmamosis was documented in bovine from Bareilly district of Uttar Pradesh.